Studying the Recent Improvements in Holograms for Three-Dimensional Display - Hamed Abbasi; Talie Zarei; Neda Jalali Farahani; Adeleh Granmayeh Rad (International Journal of Optics)
Displayers tend to become three-dimensional. The most advantage of holographic 3D displays is the possibility to observe 3D images without using glasses. The quality of created images by this method has surprised everyone. In this paper, the experimental steps of making a transmission hologram have been mentioned. In what follows, current advances of this science-art will be discussed. The aim of this paper is to study the recent improvements in creating three-dimensional images and videos by means of holographic techniques. In the last section we discuss the potentials of holography to be applied in future.